OPTIMALISASI BRANDING PRODUK UMKM ANYAMAN PANDAN DESA WONOREJO MELALUI PENDEKATAN ABCD DALAM PELAKSANAAN PROGRAM KKN (Kampelmas, 2024)
This scientific article analyzes the strategy for strengthening the branding of woven pandanus Micro, Small and Medium Enterprises (MSMEs) products in Wonorejo Village through the Asset-Based Community Development (ABCD) approach in the Community Service Program (KKN). The purpose of this research is to explore local potential that can be used to strengthen the branding of woven pandanus SMEs products and to design an ABCD approach that is in accordance with the characteristics of the people of Wonorejo Village. he research method used is qualitative research with a case study approach. The results of the study show that the natural and cultural potential of Wonorejo Village, such as the abundance of pandanus and local wisdom in woven techniques, can be used as major assets in strengthening product branding. Through the application of the ABCD approach in the KKN program, collaboration between universities, MSMEs, and local communities can increase local identity, community empowerment, and product added value. In conclusion, the ABCD approach in the KKN program provides a strong foundation for woven pandanus SMEs in building product branding that is sustainable and highly competitive.